Peripheries - Viviana González; Yesmina Urrego; Zaida Ramírez; Kelly Roca; Miguel Matallana; Paola Rey; Sandra Sarmiento; Natalia Matiz; Ángela Vanegas; Lisa Castrillón; Diego Amaya; Bibiana Ávila; et al. (Pensamiento Palabra y Obra, 2015)
Texto curatorial “Periferias”